Differential associations of specific selective serotonin reuptake inhibitors with resting-state heart rate and heart rate variability: implications for health and well-being - Kemp, Andrew H.; Fráguas, Renerio; Brunoni, Andre R.; Bittencourt, Marcio S.; Nunes, Maria A.; Dantas, Eduardo M.; Andreão, Rodrigo V.; Mill, José G.; Ribeiro, Antonio L. P.; Koenig, Julian; Thayer, Julian F.; Benseñor, Isabela M.; et al. (Psychosomatic medicine, 2016)
Objective - Debate has focused on the effects of the selective serotonin reuptake inhibitor (SSRI) antidepressants on heart rate (HR) and HR variability (HRV), both of which are predictors of adverse cardiovascular events. Here, we examine the associations between specific SSRI antidepressants and resting state HR (and HRV) after accounting for a host of potential confounding factors using propensity score techniques. - Methods - Participants included 10,466 not taking antidepressants, 46 participants taking escitalopram, 86 taking citalopram, 66 taking fluoxetine, 103 taking paroxetine, and 139 taking sertraline. HR and HRV (root mean square of successive squared differences, high frequency) were extracted from 10-minute resting-state ECGs. Analyses including propensity score weighting and matching were conducted using R-statistics to control for potentially confounding variables. - Results - Major findings indicated that users of all SSRI medications—except fluoxetine—displayed lower HRV relative to nonusers. Users of paroxetine also displayed significantly lower HRV relative to users of citalopram (Cohen's d = 0.42), fluoxetine (Cohen's d = 0.54), and sertraline (Cohen's d = 0.35), but not escitalopram. Although associations were also observed for HR, these were less robust than those for HRV. - Conclusions - Although paroxetine is associated with decreases in HRV relative to nonusers, as well as users of other SSRI medications, fluoxetine was the only medication not to display significant alterations in HR or HRV. These conclusions are limited by the cross-sectional design and nonrandomized nature of medication prescriptions. Findings highlight the importance of focusing on specific medications, rather than more heterogeneous groupings according to antidepressant action, and may have implications for health and well-being for the longer term.
Gesehen am 11.05.2020